HUBUNGAN ANTARA PEMANFAATAN MEDIA INTERNET SEBAGAI SUMBER BELAJAR TERHADAP MOTIVASI BELAJAR SISWA KELAS X AKUNTANSI SMK NEGERI 46 JAKARTA - Sintia Arlia; Ati Sumiati (Jurnal Ilmiah Econosains, 2015)
Abstract This research was aimed to obtain valid data and facts about the relationship between the use of the internet as a source of learning for class X student motivation Accounting SMK 46 Jakarta. This research was conducted by survey method with correlation approach. This study was conducted in January to February 2015. The study population was all students of SMK 46 Jakarta. Affordable population in this study were students of class X Accounting totaling 71 students. The number of samples used as research is 62 students. The sampling technique used is proportional random technique. Instruments used in the form of a questionnaire study of 20 grains to use the internet as a source of learning and 36 grains for student motivation variables. The results showed that: there is a positive relationship between utilization of the internet as a source of learning on the students motivation Grade 10 Accounting in Vocational High School 46 Jakarta. Thus if the utilization of the internet as a source increases, the learning on the students motivation will also increase. Keywords: utilization of the internet as a source, learning on students motivation.